Accuracy of Student Career Choice: Analysis of Interest and Personality Match in the Industry 4.0 Era - Aritonang, Nikon; Degeng, I Nyoman Sudana; Ramli, M; Atmoko, Adi (citeus, 2025)
This study aims to clarify the high number of college students choosing unsuitable career choices. The impact of choosing an unsuitable career path can significantly hinder the development of Indonesian human resources in the context of the industry 4.0 era. This is caused by shifting paradigms in the recruitment process of most companies or institutions that no longer prioritize a diploma as the key factor in seeking new hires. Instead, there is greater emphasis on the employee's skills, interests, creativity, and innovation, followed by a diploma and achievement index. Descriptive-qualitative design was employed. Samples were collected from college students at several universities in Surabaya using a purposive sampling technique. This study uses two assessment tests: the Lee-Thorpe test and the Myers-Briggs Type Indicator (MBTI) as predictive studies to identify which tests and subtests provide meaningful precursors for predicting students' interests and personality. The suitable career choices were facilitated through narrative and career counseling. The results show that, even when students' major didn't align with their interest and personality, proper career guidance can help them make a more suitable career choice through several adjustments. At first, students are advised to finish their degree but continue on a more suitable career according to their interest. However, if their current degree is completely incompatible, students are advised to switch to a new major which better align with their interest. Suitable career choices will help college students develop into a more robust human capital to thrive amid global competition in the industry 4.0 era.